Capitated versus fee-for-service reimbursement and quality of care for chronic disease: a US cross-sectional analysis - Tummalapalli, Sri Lekha; Estrella, Michelle M.; Jannat-Khah, Deanna P.; Keyhani, Salomeh; Ibrahim, Said (BMC health services research, 2022)
Background Upcoming alternative payment models Primary Care First (PCF) and Kidney Care Choices (KCC) incorporate capitated payments for chronic disease management. Prior research on the effect of capitated payments on chronic disease management has shown mixed results. We assessed the patient, physician, and practice characteristics of practices with capitation as the majority of revenue, and evaluated the association of capitated reimbursement with quality of chronic disease care. Methods We performed a cross-sectional analysis of visits in the United States’ National Ambulatory Medical Care Survey (NAMCS) for patients with hypertension, diabetes, or chronic kidney disease (CKD). Our predictor was practice reimbursement type, classified as 1) majority capitation, 2) majority FFS, or 3) other reimbursement mix. Outcomes were quality indicators of hypertension control, diabetes control, angiotensin-converting enzyme inhibitor or angiotensin receptor blocker (ACEi/ARB) use, and statin use. Results About 9% of visits were to practices with majority capitation revenue. Capitated practices, compared with FFS and other practices, had lower visit frequency (3.7 vs. 5.2 vs. 5.2, p = 0.006), were more likely to be located in the West Census Region (55% vs. 18% vs. 17%, p < 0.001), less likely to be solo practice (21% vs. 37% vs. 35%, p = 0.005), more likely to be owned by an insurance company, health plan or HMO (24% vs. 13% vs. 13%, p = 0.033), and more likely to have private insurance (43% vs. 25% vs. 19%, p = 0.004) and managed care payments (69% vs. 23% vs. 26%, p < 0.001) as the majority of revenue. The prevalence of controlled hypertension, controlled diabetes, ACEi/ARB use, and statin use was suboptimal across practice reimbursement types. Capitated reimbursement was not associated with differences in hypertension, diabetes, or CKD quality indicators, in multivariable models adjusting for patient, physician, and practice characteristics. Conclusions Practices with majority capitation revenue differed substantially from FFS and other practices in patient, physician, and practice characteristics, but were not associated with consistent quality differences. Our findings establish baseline estimates of chronic disease quality of care performance by practice reimbursement composition, informing chronic disease care delivery within upcoming payment models.